Carbon Fibre Reinforced Polymers applied in steel structures for improving fatigue behaviour – a short review - Ciprian Bratu; Radu Băncilă (Bulletin of the Transilvania University of Braşov, 2025)
Fatigue is a critical issue in structural engineering, characterized by the sudden and often catastrophic failure of elements subjected to cyclic loading, which can lead to significant material damage and loss of life. Carbon Fibre Reinforced Polymers (CFRP) composites is a promising alternative to traditional reinforcement methods, offering a direct, efficient, and cost-effective means to improve fatigue strength and repair damaged steel members. This paper provides a short literature review on the current advancements in the rehabilitation of steel structures, focusing on the application of CFRP for structural reinforcement. Key topics include the mechanical properties of steel and Fibre-Reinforced Polymer (FRP) composites, the bond characteristics between FRP and steel members, the fatigue performance of aged steel structures, and the current state of design codes and guidelines pertinent to FRP applications. Testing approaches from various research efforts are also examined in order to offer insights into current practices. The review highlights CFRP's economic and practical advantages, such as reduced costs for strengthening aging structures, shortened repair timelines, the ability to extend the lifespan of culturally and historically significant structures, and FRP's suitability for retrofitting steel structures due to its excellent strength-to-weight ratio and resistance to corrosion. The ease of on-site application and the low impact on traffic flow during repairs further enhance its appeal, especially for emergency repairs.
Keywords: steel structures; fibre reinforced polymers; fatigue; reinforcement